Ñakari - cultural forms of suffering after political violence in Perú - Malvaceda E., Eli (2010)
This article describes the different cultural ways of experiencing the suffering behind the political violence in Peru. It is usually assumed that everyone feel the pain similarly, is inconceivable a suffering different to the official and we intervening under the terms of our modernity, ignoring the cultural ways of experiencing the trauma, so in this article, which is part of a qualitative met.study about the psychosocial consequences of the political violence in Peru, here we present these cultural forms of suffering, such as llakis (painful memories), pinsamientuwan (recurring worries), manchay (fear, fright), iquyay (weakness) alcansu (damage), llaki nuño (scared teat), among others.